2005
DOI: 10.1007/s00199-005-0012-3
|View full text |Cite
|
Sign up to set email alerts
|

Recursive equilibrium in endogenous growth models with incomplete markets

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…6 Krebs (2006) derives the same result in a production economy with human capital accumulation. 7 In a separate class of continuous-time diffusion models, Grossman and Shiller (1982) have demonstrated that idiosyncratic risk has no effect on risk premia, simply because the cross-sectional variance of consumption growth is locally deterministic.…”
mentioning
confidence: 63%
“…6 Krebs (2006) derives the same result in a production economy with human capital accumulation. 7 In a separate class of continuous-time diffusion models, Grossman and Shiller (1982) have demonstrated that idiosyncratic risk has no effect on risk premia, simply because the cross-sectional variance of consumption growth is locally deterministic.…”
mentioning
confidence: 63%
“…Of course, in such a setting, one must also verify that the functional equation describing agent preferences in (4) can be solved on a space of bounded value functions. But, in principle, allowing for asymptotic growth in two sector models (for example, Krebs [50]) is not a problem.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the assumptions on the boundedeness of the state space can be relaxed, allowing for models with unbounded growth, for example, in the two sector incomplete markets economy studied by Krebs [50]. Using the methods in Morand and Re¤ett [62], one can use pure lattice theoretic …xed point constructions to study the operator Ah, and all the main results hold.…”
Section: ) That Proves (Ii)mentioning
confidence: 99%
See 2 more Smart Citations